2014
DOI: 10.1155/2014/161702
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Microclot Formation in an Acute Subarachnoid Hemorrhage Model in the Rabbit

Abstract: Background. Microvascular dysfunction and microthrombi formation are believed to contribute to development of early brain injury (EBI) after aneurysmal subarachnoid hemorrhage (SAH). Objective. This study aimed to determine (i) extent of microthrombus formation and neuronal apoptosis in the brain parenchyma using a blood shunt SAH model in rabbits; (ii) correlation of structural changes in microvessels with EBI characteristics. Methods. Acute SAH was induced using a rabbit shunt cisterna magna model. Extent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…The anatomy, adhesions in the subarachnoid space and cerebroventricular system in rabbits are largely different from that of humans [44]. During acute blood shunt-induced SAH [31,45,32]. Unpublished data of recent experimental studies suggest that there is no correlation between increase in ICP and amount of blood distributed in the subarachnoid space.…”
Section: Gross Examination Of Brain and Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The anatomy, adhesions in the subarachnoid space and cerebroventricular system in rabbits are largely different from that of humans [44]. During acute blood shunt-induced SAH [31,45,32]. Unpublished data of recent experimental studies suggest that there is no correlation between increase in ICP and amount of blood distributed in the subarachnoid space.…”
Section: Gross Examination Of Brain and Pathophysiologymentioning
confidence: 99%
“…These severe pathophysiological disturbances and their subsequent consequences cause early microclot formation, significant damage to the hippocampus, basal cortex and cerebral vasculature 24 h after shunt-induced SAH and triggers marked basilar artery vasoconstriction 72 h after initial bleeding [45,32,31]. Pathophysiological events caused by shunt-induced SAH are summarised in Table 2 and Fig.…”
Section: Gross Examination Of Brain and Pathophysiologymentioning
confidence: 99%
“…Platelet aggregates are found in the major cerebral arteries within two hours of experimental SAH [35]. The elevation of fibrinogen might represent microclot formation within 24 h after SAH [36]. This might be one reason for the beneficial effect of nimodipine [37], which may improve recovery from ischaemia by increasing fibrinolytic activity [38].…”
Section: Discussionmentioning
confidence: 99%
“…LS, an already well-established antihypertensive drug in daily clinical practice and well examined in preclinical and clinical settings of ischemic stroke, shows promising results by attenuating cerebral inflammation and restoring cerebral autoregulation [64,105,[122][123][124][125]. Facing preclinical aSAH research, beneficial effects of Sartans have been shown.…”
Section: Effects Of Losartan Following Asahmentioning
confidence: 99%